Suffixed Diminutive Nouns in Movies by Quentin Tarantino - Aleknaitė, Greta; Stundžia, Bonifacas (Verbum, 2024)
Language serves as a tool for expressing feelings and emotions. Diminutives play a key role in conversations by reflecting an attitude of a speaker. Consequently, this article focuses on the use of nouns with diminutive suffixes in nine movies by Quentin Tarantino. This analysis examines the meaning, formation processes and functions of suffixed diminutive nouns, categorizes them and identifies the most frequent ones, exploring their roles and comparing their usage across nine movies. The quantitative method, along with a descriptive approach, was used to study the type and token frequency of diminutive suffixes. Meanwhile, the qualitative method, combined with comparative and analytical approaches, aided in analysing the collected examples of diminutive nouns and their functions. In total, 292 common nouns, 39 different lexemes and eight diminutive suffixes were examined in this article. The most productive diminutive suffix was noted to be -ie (-y, -ey), while the most common function was ameliorative. The most prevalent diminutives were associated with close relationships.